A publicação de notícias sobre os resultados de i+d&i. Como é percebida pelos pesquisadores espanholes - Alonso-Flores, Javier; Serrano-López, Antonio Eleazar; Moreno-Castro, Carolina (InMediaciones de la Comunicación, 2018)
This study aims to know what is the perception that researchers of Spanish universities have about the impact they generated on their careers, the scientific news published with the results of their Research, Development and Innovation (R+D+I) activities. To this end, data was collected by an online survey conducted in 2016 of 602 researchers of scientific communication from 20 universities in Spain. The only requirement was that any of their publications had been subject to –at least- a press release issued by their own university in the last five years, before the survey launched (2016). For the analysis of the data, the test of the significant difference among variables (Z test) and the Kruskal-Wallis independence test, had been used. According to the results, the researchers trust more in the journalists of their institution rather than those of other media. In addition, they perceive that the dissemination of their scientific articles gives them more benefits than damages. However, these results also encourage to considering all current the challenges in the field of professionalization and scientific dissemination.